PERAWATAN BAHAN PUSTAKA PERPUSTAKAAN - Evi Endrita (UIN Imam Bonjol Padang, 2019)
Abstract : Library materials become worn out because a lot is held by the hands (especially if the hands are dirty or wet) from one user to another user and eventually can be torn. Not to mention the problem of the quality of paper as a raw material for library materials. In addition to the quality of the bindings and also the problem of storage (factors of air temperature, humidity, cleanliness of the room heat / sunlight) Adams believes that at this time the librarian should be at the same time an administrator and not a mere book collector and he considers that the technological attention of library maintenance functions is very small . Things that can invite the presence of cockroaches are the leftovers that are scattered. That is why library library is prohibited from eating or carrying food. The hand that will hold the food must also be clean free of oil stains because if the book is stained with oil it will invite the danger of Insect attack.Keyword : Library Material CareAbstrak : Bahan pustaka itu menjadi lusuh karena banyak dipegang oleh tangan (apalagi kalau tangan itu kotor atau basah) dari satu pemakai ke pemakai yang lain dan lama-lama bisa robek. Belum lagi masalah kualitas kertas sebagai bahan mentah bahan pustaka. Di samping mutu pembendelan dan juga masalah penyimpanannya (faktor suhu udara, kelembaban, kebersihan ruang panas/sinar matahari) Adams berpendapat pada saat sekarang ini pustakawan seharusnya sekaligus menjadi administrator dan bukan pengumpul buku belaka dan dia menganggap bahwa perhatian teknologi fungsi pemeliharaan bahan pustaka sangat kecil. Hal yang bisa mengundang hadirnya kecoa adalah sisa-sisa makanan yang tercecer. Itulah sebabnya mengapa di ruang baca perpustakaan dilarang makan atau membawa makanan. Tangan yang akan memegang bahan makanan juga harus bersih bebas dari noda minyak karena kalau buku itu ternoda minyak akan mengundang bahaya serangan Serangga.Kata Kunci : Perawatan Bahan Pustaka